The Dancing Cross: Contextualizing Religious Symbol in Balinese Context - Ni Made Diana Erfiani; Nyoman Tri Sukarsih; I Gusti Agung Sri Rwa Jayantini (Institut Seni Indonesia Denpasar, 2023)
Religious symbol is the generic word for all kinds of religious signs of the divine. It includes myths and religious narratives, theological ideas, particular notions such as karma or sin which are defined in one or more symbol systems, religious acts such as liturgies or private meditations that move through and overlay various symbol systems, as well as architectural and artistic symbols with religious content, books, songs, devotional objects, and the like. Generally, it can be referred to a religious object and can bear a religious meaning. This study aims to identify the meaning of a contextualized religious symbol in the Bali Church which is known as ‘the dancing cross’. The theory applied in this study is semiotic theory which in this case is structural semiotics. The source of the data are texts that discuss about the cross symbol as well as the results of interviews with the creator of the dancing cross symbol, Nyoman Darsane. This study confirms that the dancing cross, which is widely used by Christians who are members of the Protestant Christian Church in Bali is considered as the product of regionalization or contextualization of the cross which is the crux of Christian life and worship. The shape of the dancing cross is transformed from the universal shape of the cross which is consisted of two bars leading to a T-shaped cross which base stem is longer than the other three arms but crooked at the bottom like a dancer who is in left agem position. The results of the analysis through the utilization of structural semiotics in terms of syntagmatic and paradigmatic relations revealed some important points namely the contrastive meaning of the cross before and after the time of Jesus Christ as the sign of shame which covers a curse, a stumbling block and foolishness and the sign to be glorified which covers salvation victory and obedience. Other important points to be revealed are the contextual shape of the cross that can be aligned as a dancer who is in left agem position and the contextual meaning of the cross which leads to the sign of obedience of God’s people or the disciples to carry or dance the cross in accordance with the example given by Jesus Christ.